2015
DOI: 10.2166/washdev.2015.155
|View full text |Cite
|
Sign up to set email alerts
|

Combining sensor monitoring and ethnography to evaluate household latrine usage in rural India

Abstract: This paper advances research on methods used to evaluate sanitation usage and behavior. The research used quantitative and qualitative methods to contribute to new understanding of sanitation practices and meanings in rural India. We estimated latrine usage behavior through ethnographic interviews and sensor monitoring, specifically the latest generation of infrared toilet sensors, Portland State University Passive Latrine Use Monitors (PLUMs). Two hundred and fifty-eight rural households in West Bengal (WB) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Other researchers have questioned the appropriateness of sanitation facilities for women. 35 43 Consistent with research that found toilets only to be used for defection, 44 few women in our study used toilets to urinate or manage menstruation; women considered toilets unsuitable for these needs. Globally, menstrual hygiene is gaining recognition as a public health issue, 45 but remains ‘largely absent from the sanitation vocabulary’.…”
Section: Discussionsupporting
confidence: 84%
“…Other researchers have questioned the appropriateness of sanitation facilities for women. 35 43 Consistent with research that found toilets only to be used for defection, 44 few women in our study used toilets to urinate or manage menstruation; women considered toilets unsuitable for these needs. Globally, menstrual hygiene is gaining recognition as a public health issue, 45 but remains ‘largely absent from the sanitation vocabulary’.…”
Section: Discussionsupporting
confidence: 84%
“…Despite these limitations, this study furthers research on the methods for assessing latrine use in low-income settings and adds to a growing body of evidence on the feasibility of instrumented monitoring of sanitation behavior at the household level 14,39. This is particularly significant in the context of latrine use assessment since such alternatives are likely to offer a viable low-cost, objective, non-invasive and medium to long-term perspective of use.…”
Section: Discussionmentioning
confidence: 86%
“…In July 2018, this study found an estimated 21.7% of rural households in Rajasthan with access to a toilet still had one or more members engaging in OD practices. This highlights the importance of sanitation campaigns to construct toilets and to incorporate behaviour change practices that increases use of the toilets 28–34. Regular toilet usage is one of the important aspects of the second phase of SBM called ODF Plus and promotes sustained use of sanitation facilities.…”
Section: Discussionmentioning
confidence: 99%